Oxidação foto-eletroquímica como rota alternativa para a produção de derivados da biomassa - Moreti, Lauren dos Santos (Universidade Federal de São Carlos, 2021)
The need of fossil fuel replacement as energy source is urgent. Once the solar light has high incidence on Earth, it can be used as an alternative energy source to be directly converted into electric energy or to be stored as chemical bonds. In this sense, the molecular hydrogen production in photoelectrochemical cells (PEC) could provide an interesting energy carrier to be employed in chemical industry or in fuel cells devices. The PEC can be fed with water (the so-called water splitting process) or alternatively, with organic molecules as electron and protons sources. The organic molecule oxidation opens the possibility to achieve added-value products in the anode, besides the H2 in the cathode. As an example, the 5-hidroximethylfurfural (5-HMF), a derivative from glucose, can be oxidized to 2,5-furandicarboxilic acid (FDCA), an important molecule in the fuel production and polymers synthesis. Nowadays, the FDCA production is performed through petroleum derivatives, which is extremely undesired. The literature brings several catalysts able to perform the 5-HMF oxidation to FDCA based on electro or photoelectrochemical devices allowing the H2 production.
Photo-electrochemical oxidation as an alternative route for biomass derivatives products production
Keywords: 5-hidroximetilfurfural; Fotoeletroxidação; Biomassa.; 5-hidroximethylfurfural; Photoelectrooxidation; Biomass; CIENCIAS EXATAS E DA TERRA::QUIMICA